2008
DOI: 10.1007/s10389-008-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Does shisha smoking affect blood pressure and heart rate?

Abstract: Aim The aim of this investigation was to explore the correlation of shisha smoking with blood pressure and heart rate values. Subjects and methods This is a randomized cross-sectional epidemiological study involving a total of 14,310 adults selected from various regions of Jordan. Well-trained pharmacy students interviewed participants in outpatient settings. The frequencies of water-pipe-smoking males and females in the sample were 21.11% and 10.27%, respectively. Measures of blood pressure and heart rate val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 17 publications
(24 reference statements)
6
22
0
Order By: Relevance
“…[1][2][3][4][5] It is suspected to be a risk factor for a number of acute and chronic tobacco-related defects and/or diseases. [1][2][3][4][5][6][7][8] Among the deleterious effects of narghile use, the chronic cardiorespiratory defects are prominent: [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] exclusive narghile smokers (ENS) have been shown to exhibit worse respiratory and cardiac profiles than healthy non-smokers (HNS) (eg, higher heart rate and systolic (SBP) and diastolic (DBP) blood pressures and lower lung flows and/or volumes). In addition, studies have demonstrated acute (immediate) effects of narghile smoke in the form of increased heart rate, breathing frequency, expired carbon monoxide, SBP, or DBP and a decline in lung function.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] It is suspected to be a risk factor for a number of acute and chronic tobacco-related defects and/or diseases. [1][2][3][4][5][6][7][8] Among the deleterious effects of narghile use, the chronic cardiorespiratory defects are prominent: [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] exclusive narghile smokers (ENS) have been shown to exhibit worse respiratory and cardiac profiles than healthy non-smokers (HNS) (eg, higher heart rate and systolic (SBP) and diastolic (DBP) blood pressures and lower lung flows and/or volumes). In addition, studies have demonstrated acute (immediate) effects of narghile smoke in the form of increased heart rate, breathing frequency, expired carbon monoxide, SBP, or DBP and a decline in lung function.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most water pipe smokers are unaware of the dangers of water pipe smoking and consider it a safe alternative to cigarette smoking [2,5,6]. However, smoke from the water pipe contains many of the carcinogens and toxic elements found in cigarette smoking, such as monoxide, nicotine, tar and heavy metals [3,7], and therefore may lower quality of life [8,9] as it is associated with various poor-health outcomes [10,11]. A recent systematic review of the health effects of water pipe smoking showed that it was significantly associated with lung cancer, respiratory illness, low birth weight and periodontal disease [12].…”
Section: Introductionmentioning
confidence: 99%
“…3 Ultimately, in chronic shisha smokers, systolic blood pressure and heart rate remain signifi cantly elevated. 17 People who smoked both shisha and cigarettes were reported to have the highest mean systolic blood pressure and heart rate, across all age groups. 17 NO, a vasodilator, was found at a signifi cantly higher serum concentration in shisha smokers (34.3 µmol/l) compared with non-smokers (22.5 µmol/l).…”
Section: The Health Effects Of Smoking Shishamentioning
confidence: 96%
“…17 People who smoked both shisha and cigarettes were reported to have the highest mean systolic blood pressure and heart rate, across all age groups. 17 NO, a vasodilator, was found at a signifi cantly higher serum concentration in shisha smokers (34.3 µmol/l) compared with non-smokers (22.5 µmol/l). 18 It was reported that shisha smokers showed impaired vasodilation of the brachial artery in response to shear stress, compared with that of cigarette smokers and non-smokers.…”
Section: The Health Effects Of Smoking Shishamentioning
confidence: 96%